Improving Student Creativity with Reading Literacy in the Moriah Theological High School Library - Nofi Emelan Haning; Vince Sarlina Dawa; Mutya Arini Saekoko; Widjaja Sugiri (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2022)
Many factors lead to the low quality of learning, including the not yet fully utilized learning resources, both by lecturers and students. The library is a reference source of learning for students, so we need a quality and ideal library. One of the supports as a learning resource that must be held by schools is the use of the school library. This study aims to determine the role of the school library in providing learning resources at Moriah Theological College. The research method used in this study is descriptive qualitative with the APTE Model (Needs Analysis, Training, Action, and Evaluation). Observations were made directly in the library regarding the infrastructure of the library. Documentation, namely a list of books, a list of loans, and library visitor data. The results of the research conducted can be said that the library of the Moriah Theological College has a good role in supporting learning, namely as an educational, informative facility, and the library at the Sekolah Tinggi Teologi Moriah in terms of facilities and infrastructure has met library standards well. Banyak faktor yang menyebabkan rendahnya kualitas pembelajaran di antaranya yaitu belum dimanfaatkannya sumber belajar secara maksimal, baik oleh dosen maupun mahasiswa. Perpustakaan merupakan acuan sumber belajar bagi mahasiswa, sehingga diperlukan suatu perpustakaan yang berkualitas dan ideal. Salah satu pendukung sebagai sumber belajar yang harus diadakan oleh sekolah adalah dimanfaatkannya perpustakaan sekolah. Penelitian ini bertujuan untuk mengetahui peran perpustakaan sekolah dalam penyediaan sumber belajar di Sekolah Tinggi Teologi Moriah. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan Model APTE (Analisis kebutuhan, Pelatihan, Tindakan, dan Evaluasi). Observasi dilakukan langsung di perpustakaan mengenai sarana prasarana yang ada di perpustakaan. Dokumentasi yaitu daftar buku-buku, daftar peminjaman dan data pengunjung perpustakaan. Hasil penelitian yang dilakukan dapat dikatakan perpustakaan Sekolah Tinggi Teologi Moriah memiliki peran yang baik dalam menunjang suatu pembelajaran, yaitu sebagai sarana edukatif, informatif, dan perpustakaan di Sekolah Tinggi Teologi Moriah dari segi sarana dan prasarana sudah memenuhi standar perpustakaan dengan baik.